Study on Form, Drainage Network, and Watershed Hydrograph by Using SIMODAS (Case Study on Sabu Island - Nusa Tenggara Timur) - Wirosoedarmo, Ruslan; Haji, A. Tunggul Sutan; Pramesti, Erlita Meidya (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Watershed management includes the identification of linkages between land use, soil, and water; between the upstream and downstream area; and a system in the hydrology which consists of the system input and system output. The system output from one river basin system is the flood discharge river which is the integrator that influenced by catchment area. River flood discharge is affected by wheather Watershed acts as a regulator of the process especially in terms of hydrology. Â Hydrograph form, in general, is strongly influenced by the nature of the rainfall, the length of the main stream slope, the direction and shape of the watershed. Â Research was conducted in Sabu Island, Nusa Tenggara Timur. The method used was the spatial analysis and flood hydrographs. Data processing was done by displaying spatial data in Arc View to perform the cutting process Daieko watershed, Ladeke and Rainkore. Then, it was processed in data Elevetion Model (DEM) of each watershed by Arc View. Â The results showed that Ladeke Watershed is the most potential to flooding from the Daieko and Rainkore with the flood peak was always high. Form of bird feathers watershed flood peak discharge value was small with relative long time. Form a broad basin with a river pattern of spread (radial) tended to produce values of flood peak discharge. Radial form of the most sensitive watersheds and smallest form parallel to the change of land was due to increasing flood discharge.Keywords: shape of watershed, the hydrograph, SIMODAS